Pengaruh Produk, Harga, Promosi, Distribusi Terhadap Keputusan Konsumen Membeli Produk Sepeda Motor Merek Yamaha Tipe Jupiter Z Di Kabupaten Ketapang - Jon Wahyudi (JURNAL MANAJEMEN MOTIVASI, 2014)
The purpose of this research is to analyze the influence of the marketing mix for the consumer decision to buy the product brand motorcycle Yamaha Jupiter - type Z. The shape of this research is descriptive with a sample of 100 people. Population defined in this study are all consumers Yamaha Jupiter Z in 2010-2012 in Ketapang with sampling technique is purposive sampling and analysis tool used is multiple regression. The results of this study indicate that the marketing mix consists of product, price, promotion, distribution channels simultaneously significantly influence the consumer's decision to buy Yamaha Jupiter Z Brand in Ketapang. While partially only products and distribution channels that influence the consumer's decision to buy Yamaha Jupiter Z Brand in Ketapang. Product, price, promotion, and distribution channels affect consumers' decision to buy Yamaha Jupiter Z Brand in Ketapang by 78.20 % while the remaining 21.80 % influenced by other variables outside of this research.